2021
DOI: 10.1080/15475441.2021.1941032
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Read Interacts with Children’s Spoken Language Fluency

Abstract: Until at least the end of adolescence, children articulate speech differently than adults. While this discrepancy is often attributed to the maturation of the speech motor system, we sought to demonstrate that the development of spoken language fluency is shaped by complex interactions across motor and cognitive domains. In this study, we specifically tested for a relationship between reading proficiency and coarticulatory organization, a fundamental correlate of spoken language fluency, used for both reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
(126 reference statements)
1
4
0
Order By: Relevance
“…Another important contribution of this study is the link we observed between speech sound production and phonological decoding, a critical basis for reading skills. This is in line with recent findings by Popescu and Noiray (2021), who report less intersegmental co-articulation in pseudoword production in a group of more proficient German readers. Here, we expand on this finding by showing a relationship between better phonological decoding skills, suggesting also better reading skills, and faster preparation and initiation of speech sound production.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Another important contribution of this study is the link we observed between speech sound production and phonological decoding, a critical basis for reading skills. This is in line with recent findings by Popescu and Noiray (2021), who report less intersegmental co-articulation in pseudoword production in a group of more proficient German readers. Here, we expand on this finding by showing a relationship between better phonological decoding skills, suggesting also better reading skills, and faster preparation and initiation of speech sound production.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, this study and the two studies that also observed an association between reading-related and articulatory skills (Noiray, Popescu, et al, 2019;Popescu & Noiray, 2021) were conducted in orthographically transparent languages. Future research should examine whether the same effects are present in orthographically opaque languages.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…And then, even once typically-developing children shed these early phonological errors, they still don't master appropriate amounts of coarticulatory overlap until puberty (Zharkova, Hewlett, Hardcastle, & Lickley 2014). Until that time, children exhibit excessive intra-syllabic coarticulation in their speech, and are only able to distinguish between adjacent segments as their fine motor control develops, the lexicon grows, and phonological awareness increases (Barbier et al 2020, Noiray et al 2019, Popescu & Noiray 2021, Zharkova, Hewlett, & Hardcastle 2011. Thus, children exhibit protracted coarticulatory development until early adolescence when they have acquired both sufficient linguistic and speech-motor experience to approximate adult-like segmental overlap.…”
Section: Measures Of Phonetic Variabilitymentioning
confidence: 99%